2022
DOI: 10.54883/wish.v1i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the Event of Premature Rupture of Membrane in Muna Regency Hospitals

Abstract: Background : One of the maternal health programs is to accelerate the decline in numbers. Maternal mortality and maternal mordibity. One ofe the causes of maternal death is infection that can be caused by premature rupture of membranes. Methods : This research was quantitative with a cross sectional study design. Study has been carried out in September 2021. The research sample is 164 people obtained by simple random sampling. Processed data using the chi square test. Result : The result showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on data literature review from research by 35 Anemia is a condition in which red blood cells / hemoglobin (Hb) have decreased in number, so that the oxygen carrying capacity for the needs of vital organs in pregnant women is reduced. The capacity of the blood to carry oxygen is low, spurring the heart to increase cardiac output.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on data literature review from research by 35 Anemia is a condition in which red blood cells / hemoglobin (Hb) have decreased in number, so that the oxygen carrying capacity for the needs of vital organs in pregnant women is reduced. The capacity of the blood to carry oxygen is low, spurring the heart to increase cardiac output.…”
Section: Resultsmentioning
confidence: 99%
“…Based on data literature review from 35 the results showed that there was a relationship between anemia and the incidence of PROM, with a value of p=0,438.…”
Section: Resultsmentioning
confidence: 99%